(untitled) (World Bulletin of Public Health, 2022)
In women worldwide the most common malignant neoplasm is breast cancer, with a lifetime risk of 1 out of every 8 women. The association between Bcl-2 and breast cancer development and progression is still unclear, but a relationship between unfavorable clinical outcome and Bcl-2 overexpression is to be expected. The aim of this study is the detection of Bcl-2 in breast cancer tissues, utilizing the immunohistochemical methods and its association with various clinicopathologic parameters as age, family history, grade and stage.